National comparative audit of the use of platelet transfusions in the UK. - Qureshi, H; Lowe, D; Dobson, P; Grant-Casey, J; Parris, E; Dalton, D; Hickling, K; Waller, F; Howell, C; Murphy, M (2007)
The objective of this national audit was to examine the use of platelet transfusions against audit standards developed from national guidelines. Hospitals were asked to provide data on 40 consecutive patients receiving platelet transfusions (15 haematology patients, 10 cardiac, 10 critical care and five in other clinical specialties). One hundred and eighty-seven UK hospitals participated, including 168/263 (64%) hospitals in England. A total of 4421 patients receiving platelet transfusions were audited. The reason for transfusion was documented in the medical records for 93% of transfusions and 57% were used for prophylaxis (in the absence of bleeding). Overall 3726/4421 (84%) of the transfusions were evaluable and 43% (1601/3726) were found to be non-compliant with the audit standards. A major non-compliance was failure to measure the platelet count before transfusion (29% of transfusions). Other non-compliances included the use of platelet transfusion in the absence of bleeding in 11% of cardiac surgery patients receiving platelet transfusions, the use of a threshold platelet count more than 10 x 10(9)/L for 60% of prophylactic platelet transfusions in haematology patients without risk factors indicating the need for a higher threshold, and a threshold platelet count more than 30 x 10(9)/L for 59% of prophylactic platelet transfusions in critical care. The reasons for the high rate of non-compliance were not explored in this audit, but this is a topic worthy of further study. The main recommendations were that hospitals should ensure there are written local guidelines for platelet transfusions, clinicians must be provided with training about their appropriate use, and hospitals should carry out regular audits of practice. More research should be carried out to develop the evidence base for the use of platelet transfusions, more detailed guidelines should be developed for platelet transfusions in critical care and cardiac surgery, and the audit should be repeated in about three years.